The role of rare earth elements and dietary intake in tongue cancer: a mediation analysis in southeast China - Wang, Na; Liu, Fengqiong; Chen, Yujia; Xie, Manling; Gao, Bingju; Qiu, Yu; Lin, Lisong; Shi, Bin; Chen, Fa; He, Baochang (Frontiers in Public Health, 2023)
Objective The current research aimed to examine how dietary intake and rare earth elements may affect the development of tongue cancer. Methods The serum levels of 10 rare earth elements (REEs) in 171 cases and 171 healthy matched controls were measured by inductively coupled plasma mass spectrometry (ICP-MS). The conditional logistic regression was used to examine the relationship between dietary intake, serum levels of 10 REEs, and tongue cancer. Mediation effect and multiplicative interaction analysis were then performed to estimate the potential contribution of REEs in dietary intake associated with tongue cancer. Results Compared with the control group, patients with tongue cancer consumed significantly less fish, seafood, fruit, green leafy vegetables, and non-green leafy vegetables, with higher serum praseodymium (Pr), dysprosium (Dy), and lanthanum (La) levels, and lower serum cerium (Ce) and scandium (Sc) levels. The interaction effect was observed between some REEs and food categories. Green vegetables' impact on the risk of tongue cancer is partially attributed to the La and Thorium (Th) elements (P < 0.05, the mediated proportion were 14.933% and 25.280%, respectively). The effect of non-green leafy vegetables for tongue cancer mediated via Pr, Dy, and Th (P < 0.05, the mediated proportion were 0.408%, 12.010%, and 8.969%, respectively), and the Sc components in seafood (P < 0.05, the mediated proportion was 26.120%) is partly responsible for their influence on the risk of tongue cancer. Conclusion The correlation between REEs and dietary intakes for tongue cancer is compact but intricate. Some REEs interact with food intake to influence tongue cancer, while others act as a mediator.